2003
DOI: 10.1128/aem.69.2.835-844.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Composition Affects Soil Fungistasis

Abstract: Most soils inhibit fungal germination and growth to a certain extent, a phenomenon known as soil fungistasis. Previous observations have implicated microorganisms as the causal agents of fungistasis, with their action mediated either by available carbon limitation (nutrient deprivation hypothesis) or production of antifungal compounds (antibiosis hypothesis). To obtain evidence for either of these hypotheses, we measured soil respiration and microbial numbers (as indicators of nutrient stress) and bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 43 publications
5
70
2
6
Order By: Relevance
“…Most previous studies indicated that associations between bacteria and fungi were antagonistic rather than synergistic (Flegler et al 1974, Padgett 1993, Moller et al 1999, Mille-Lindblom & Tranvik 2003, Mille-Lindblom et al 2006a. Despite inhibition by bacteria, fungi have been found to dominate litter decomposition processes in both aquatic and terrestrial systems (de Boer et al 2003). Unfortunately, because of the large variations in fungal biomass, the results from the present study are inconclusive.…”
Section: Discussioncontrasting
confidence: 55%
“…Most previous studies indicated that associations between bacteria and fungi were antagonistic rather than synergistic (Flegler et al 1974, Padgett 1993, Moller et al 1999, Mille-Lindblom & Tranvik 2003, Mille-Lindblom et al 2006a. Despite inhibition by bacteria, fungi have been found to dominate litter decomposition processes in both aquatic and terrestrial systems (de Boer et al 2003). Unfortunately, because of the large variations in fungal biomass, the results from the present study are inconclusive.…”
Section: Discussioncontrasting
confidence: 55%
“…Hence, for the abandoned arable soil a better fungal growth in woodblocks as compared to sawdust may be caused by a lower competitive pressure of bacteria. A negative effect of bacteria on fungal growth has been suggested to be due to bacterial release of lytic enzymes degrading fungal cell walls, to the production of antifungal compounds (antibiotics) or to the competition for available organic compounds between bacteria and fungi (De Boer et al 2003;Romani et al 2006). Since there is a lower decomposition rate in sawdust as compared to woodblocks, we assume that there are negative effects (antagonism) of bacteria on fungi and vice versa resulting in a net lower decomposition.…”
Section: Soil Originmentioning
confidence: 99%
“…V102. P. fluorescens Pf0-1 was isolated from an agricultural loam soil in Sherborn (MA, USA), whereas the other strains were isolated from a coastal dune site in The Netherlands (Compeau et al, 1988;de Boer et al, 2003de Boer et al, , 2007. This coastal dune soil does also contain pseudomonads that are closely related to P. fluorescens Pf0-1 (de Boer et al, 2007).…”
Section: Bacterial Cultures and Growing Conditionsmentioning
confidence: 99%